Regulation of HER2 Oncogene Transcription by a Multifunctional Coactivator/Corepressor Complex - Garee, Jason P. (Endocrine Society, 2014)
Transcription of the HER2 oncogene can be repressed by estrogen (E2). We now show that, a splice isoform of the nuclear receptor coactivator AIB1, AIB1-Δ4, is able to reverse E2 repression of HER2 gene expression in breast cancer cells. The first 224 amino acids of AIB1 that are absent in AIB1-Δ4, bind a co-repressor, ANCO1. Using chromatin immunoprecipitation assay approaches in MCF7 and BT474 cell lines, we demonstrate that AIB1 and AIB1-Δ4 can bind to the E2 regulatory site in the first intron of the HER2 gene, after E2 treatment, but only full-length AIB1 recruits ANCO1. Consistent with E2-induced chromatin repression, the AIB1-ANCO1 complex recruits HDAC3 and HDAC4 to the intronic estrogen response element and the proximal promoter acquires the repressive chromatin mark H3K9me3 and loses H3K4me1. In contrast, AIB1-Δ4 does not recruit ANCO 1, HDAC3, or HDAC4 and the proximal promoter retains activation marks of H3K4me1. In cell lines with low levels of ANCO1 (T47D), E2 does not repress HER2 gene transcription but the repressive response can be restored by overexpression of ANCO1. ANCO1 can also repress other E2-responsive genes, indicating that AIB1, AIB1-Δ4 and ANCO1 are important determinants of endocrine and growth factor responsiveness in breast cancer.